Noncytopathic hepatitis A virus induces surface alterations in LLC-MK2 cells revealed by thin sections, negative staining, and scanning electron microscopy - Hernández-Chavarría, Francisco (2002)
Previous electron microscope studies of ultrastructural events during hepatitis A virus replication in experimentally infected cells have used only ultrathin section techniques. Nevertheless, no important differences were observed between infected and uninfected cells. This study was carried out using scanning electron microscopy and negative staining of whole LLC-MK2 cells grown directly on grids covered with support membranes, and then infected with an hepatitis A virus strain. Thin sections of infected and unifected controls were also analyzed. An intricate web of projections forming a net between cell interfaces was observed only in infected cells. Some of these projections were more than 700 nm long and had ballooning tips. Nevertheless, HAV particles were not visualized in the infected cells.